Metrics for conceptualizing sustainable diets at local level in Vietnam - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The conceptual framework and set of minimum metrics identified in consultation with 50 Vietnamese stakeholders, expert interviews, and characterized datasets as part of A4NH's country coordination and engagement efforts. The framework, accompanying metrics, and key leverage points likely to have an impact across multiple-sectors related to the food system.